Facile Fabrication of Ag Nanocrystals Encapsulated in Nitrogen‐doped Fibrous Carbon as an Efficient Catalyst for Lithium Oxygen Batteries. Issue 2 (12th March 2021) - Liu, Lili; Ma, Tianyi; Fang, Weiwei; Liu, Yuqing; Konstantinov, Kostantin; Wang, Jiazhao; Liu, Hua‐Kun
Abstract : A facile synthesis of Ag nanocrystals encapsulated in nitrogen‐doped carbon fiber (NCF) is proposed, based on the simultaneous reaction between pyrrole and Ag + ions in an aqueous solvent followed by a heat treatment. The as‐prepared Ag/NCF demonstrated superior catalytic behavior toward ORR and OER. Besides improved cycling stability, a much lower discharge/charge gap of 0.89 V (vs Li/Li + ) compared with 1.38 V for NCF cathode with a fixed capacity of 500 mAh g −1 was obtained in lithium oxygen batteries. The introduction of Ag crystals into NCF facilitates the oxygen reduction reaction/oxygen evolution reaction kinetics. X‐ray diffraction analysis coupled with Raman spectroscopy confirmed that Ag/NCF cathode could reversibly catalyze Li2 O2 formation and decomposition. The NCF matrix offers a conductive network to realize rapid mass transfer and the encapsulated Ag nanocrystals supplied effective catalytic active sites. The combined action between both contributes to the superior electrocatalytic performance. Abstract : A Ag nanocrystals encapsulated in nitrogen‐doped carbon fiber (NCF) cathode synthesized by a facile redox reaction between pyrrole and Ag + demonstrates reduced discharge/charge overpotential and stabilized cycling performance for aprotic Li–O2 batteries.